Roberta L. Salper, Valle Inclán y su mundo: ideología y forma narrativa. Rodopi, Amsterdam, 1988; 232 pp. - Lima, Robert (El Colegio de México, 1990)
Se reseñó el libro: Valle Inclán y su mundo: ideología y forma narrativa.